Analysis Of the Selection of Travel Routes Based On The Driver’s Working Time - Maciej GLINIAK; Arkadiusz BIESZCZAD; Beata CHUDY; Piotr HODUREK (Communications of International Proceedings, 2023)
The aim of the work was to analyze the selection of travel routes based on the driver's working time. A detailed analysis of the driver's working time was carried out in the work, which allowed to check how much time the driver takes for individual activities in the implementation of a transport order. The work presents the characteristics of drivers' work and the risks that may occur during transport. It also presents ways to control vehicles, drivers' working time and possible ways to improve it. The data obtained from a transport company providing international transport allowed to select the routes that deviate the most from the assumed standard and, based on them, to optimize in order to shorten the working time and the number of kilometers. Then, the remaining time for the driver was calculated, as well as the number of kilometers that the driver would be able to cover if he used the driving time to the maximum.
Keywords: travel route; driving; time; driver’s work